R and MATLAB - Hiebeler, David E. (Chapman & Hall/CRC the R series (CRC Press), 2015)
The First Book to Explain How a User of R or MATLAB Can Benefit from the OtherIn today's increasingly interdisciplinary world, R and MATLAB® users from different backgrounds must often work together and share code. R and MATLAB® is designed for users who already know R or MATLAB and now need to learn the other platform. The book makes the transition from one platform to the other as quick and painless as possible. Enables R and MATLAB Users to Easily Collaborate and Share CodeThe author covers essential tasks, such as working with matrices and vectors, writing functions and other programming co.